The Development of a Fire Alarm System which can Identify the Location of the Incident on Google maps through the 4G Internet Network: https://doi.org/10.69692/SUJMRD0901188 - Khongsomboon, Khamphong; Sengthippani, Tick; Didtaphong, Xaysamone; Phanthongsy, Phosy; Panyanouvong, Nouanchanh; Insankeovilay, Souksamai; Phommasoulin, Souvanhny; Sisaat, Khamphao (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
According to the statistics of fire occurrence in Laos during 2014 – 2020, a total of 1,195 cases of fire were witnessed resulting in the loss of more than 2,391,000,000,000 LAK. During the last 7 years, 383 of which (32%) happened in Vientiane Capital which was recorded as the highest number of fire incidents, and herein the loss reached 1,147,338,000,000 kip. The fire is not only cause of death, but it also burns belongings and destroys the shelters of the victims, and affect livelihood. Thus, this reason leads a great challenge to the current firefighting approach since its process takes a long time. The cause of a very slow process might be that the concerned parties have to inquire the relative information from victims, especially the address of place where fire occurs; it can take 10 to 30 minutes to get clear information. Besides, the electrical office also needs such detail to cut off the electricity supplied to the fire area. As consequence of these, the purpose of this research is to develop the fire alarm system that can point out the fire location with giving the directions in Google Maps via internet 4G with data transmission speed of less than 1 minute. The methodologies are that, when the fire happens, the transmission system will alert then send the information to the firefighting station, electrical station and traffic police station within less than 1 minute through the 4G communication. The results revealed that the experimented in 10 transmission station can sending the information of the measurement point to the center. It showed that the average speed is 7.28 seconds. The given information includes the contact details of homeowners, location addresses and directions. It can be more useful in extinguishing a starting fire that threatens life, property and environment as well as in rescuing people from dangerous situations.